P and S velocity tomography of the Mariana subduction system from a combined land‐sea seismic deployment. (11th March 2015) - Barklage, Mitchell; Wiens, Douglas A.; Conder, James A.; Pozgay, Sara; Shiobara, Hajime; Sugioka, Hiroko
Abstract Seismic imaging provides an opportunity to constrain mantle wedge processes associated with subduction, volatile transport, arc volcanism, and back‐arc spreading. We investigate the seismic velocity structure of the upper mantle across the Central Mariana subduction system using data from the 2003–2004 Mariana Subduction Factory Imaging Experiment, an 11 month deployment consisting of 20 broadband seismic stations installed on islands and 58 semibroadband ocean bottom seismographs. We determine the three‐dimensional VP and VP/VS structure using over 25, 000 local and over 2000 teleseismic arrival times. The mantle wedge is characterized by slow velocity and high VP/VS beneath the fore arc, an inclined zone of slow velocity underlying the volcanic front, and a strong region of slow velocity beneath the back‐arc spreading center. The slow velocities are strongest at depths of 20–30 km in the fore arc, 60–70 km beneath the volcanic arc, and 20–30 km beneath the spreading center. The fore‐arc slow velocity anomalies occur beneath Big Blue seamount and are interpreted as resulting from mantle serpentinization. The depths of the maximum velocity anomalies beneath the arc and back arc are nearly identical to previous estimates of the final equilibrium depths of mantle melts from thermobarometry, strongly indicating that the low‐velocity zones delineate regions of melt production in the mantle. The arc and back‐arc melt production regions are well separated at shallow depths, but may be connected at depths greater than 80 km.